Features of the constituent process in the activity of the Ministry of Internal Affairs of Ukraine (Law and Safety, 2018)
The constituent process as a kind of legal process has been researched. Its specific features in the activity of the Ministry of Internal Affairs of Ukraine include the fact that it is the result of legal regulation, not related to the existence of a dispute about the right; consists of a certain sequence of proceedings (in regard to agencies and units – creation, reorganization and liquidation, in regard to officials – appointment and removal); aimed at the formation, development and improvement of the institutional and personnel basis of the Ministry of Internal Affairs; acts as a special regulatory procedure for carrying out management activity of the implementation of the relevant legal norms; ensures the effective functioning of the state administration mechanism in the relevant field.On the basis of theoretical analysis of legal literature, the author has determined that the regime of the constituent process in the activity of the Ministry of Internal Affairs first in its general theoretical aspect distinguishes, first of all the specificity of the formation of the corresponding agencies and units of the state or the appointment of officials depending on their subordinate position within the structure of the Ministry, in particular, and the mechanism of the state in general. It has been argued that the purpose of the constituent process is the formation, development and improvement of the relevant agencies and units, the appointment of officials, as well as their management.It has been determined that the reasons for the origin of this type of legal process in the activity of the Ministry of Internal Affairs are the relevant legal facts or legal status. One can study the main elements of the procedural form in the constituent process in the activities of the Ministry of Internal Affairs, which combine the specific features and characteristics of each type of legal process.